Treating Comorbid Opioid Use Disorder in Chronic Pain - Matthews, Annette M.; Fellers, Jonathan C. (Springer International Publishing : Imprint: Springer, 2016)
This in-depth text addresses how to approach and treat the chronic pain patient struggling with problematic opiate use. It discusses the approach for patients who may be at high risk of problematic use, such as those with a history of mental illness or substance use disorder. The first part covers diagnosis and treatment, focusing on common best practices that practitioners can adapt to any practice. Two of the chapters detail alternative and replacement therapies for opiates. Two more cover special issues in the treatment of women and older patients. The second part reviews the ethical, legal, regulatory, and policy issues surrounding the treatment of patients with comorbid pain and addiction. The book includes strategies for documentation that mitigate the risk of legal issues or ethical boundary crossings. The last part of the book addresses treating comorbid pain and opiate abuse in different medical settings and the treatment of co-occurring mental illnesses and substance abuse. Treating Comorbid Opioid Addiction and Dependence in Chronic Pain is of great value to psychiatrists, pain physicians, primary care providers, social workers, drug rehabilitation centers, and other behavioral health professionals. .